Thessalonique et les réfugiés, 1922-1930 : une mutation urbaine singulière - Vilma Hastaoglou-Martinidis (Cahiers Balkaniques)
Abstract: in Thessaloniki, the arrival of refugees in 1922 and 1923 (after the exchange of populations between Greece and Turkey) marked a turning point in the development of the city. The consequences of the influx of refugees there were particularly intense, due to the scale of the wave and the fact that they were combined with the reconstruction of its intramural center after the fire of 1917, the upheaval of its multi-ethnic character, and the reorientation of the city’s economy within the new national territory after the loss of the Balkan hinterland in 1912. This presentation dwells on the spatial implications of this unique process, which includes the geographical distribution of refugees, the accommodation in tradable properties, the foundation and construction of their neighborhoods, the sites of their economic activity, and the repercussions on the size and shape of the urban space.